(untitled) (Publicaciones en Ciencias y Tecnología, 2009)
The Automation is essential for the production of consumer goods worldwide. Research in this area introduces the institutions involved in technology transfer process to develop more complex systems. In 2008, between UPC and UNEXPO adopting a Technology Transfer Program. Distance education is now a great need for modern society. For this we have developed a plataform dedicated to the transmission of knowledge. However, in the area of Engineering, is essential, not only the transfer of knowledge, which is in person, but also the development of skills that are obtained by putting knowledge into practice with this platform It manages the training of researchers that will serve as multipliers to provide courses and practical activities. By virtue of its importance, received funding to various companies for the development of remote communication platforms with networking opportunities.